2015
DOI: 10.1074/jbc.m114.624213
|View full text |Cite
|
Sign up to set email alerts
|

Heart Mitochondrial TTP Synthesis and the Compartmentalization of TMP

Abstract: Background:The ability of TMP to serve as a precursor of mitochondrial synthesis of TTP is not well understood. Results: TMP cannot be converted to TTP except by breakdown to thymidine in isolated mitochondria. Conclusion: Thymidine is the sole source for TTP synthesis in the mitochondrial matrix. Significance: Thymidine salvage in mitochondria is crucial to understand mitochondrial DNA depletion diseases caused by mitochondrial thymidine kinase (TK2) deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Despite the clear benefits of this therapy, we observed that most of the dCMP and dTMP were rapidly converted to their respective nucleosides, dC and dT, suggesting that these nucleosides were the active therapeutic agents. In support of our hypothesis, a study of mitochondria isolated from hearts of rats treated with radiolabeled dT and dTMP demonstrated that most of the mitochondrial TTP was generated from dT, rather than dTMP, and that exogenously administered dTMP was compartmentalized from dTMP synthesized from dT …”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Despite the clear benefits of this therapy, we observed that most of the dCMP and dTMP were rapidly converted to their respective nucleosides, dC and dT, suggesting that these nucleosides were the active therapeutic agents. In support of our hypothesis, a study of mitochondria isolated from hearts of rats treated with radiolabeled dT and dTMP demonstrated that most of the mitochondrial TTP was generated from dT, rather than dTMP, and that exogenously administered dTMP was compartmentalized from dTMP synthesized from dT …”
Section: Discussionsupporting
confidence: 67%
“…In support of our hypothesis, a study of mitochondria isolated from hearts of rats treated with radiolabeled dT and dTMP demonstrated that most of the mitochondrial TTP was generated from dT, rather than dTMP, and that exogenously administered dTMP was compartmentalized from dTMP synthesized from dT. 20 In the present study, we initially tested a dose of 260mg/kg/day of dC1dT, which is the equimolar concentration of 400mg of dCMP1dTMP, and subsequently 520mg/kg/day of dC1dT. Interestingly, we observed that Tk2 -/-260 dC1dT mice had a life span equivalent to that of Tk2 -/-200 dCMP1dTMP , whereas Tk2 -/-520 dC1dT had a life span equivalent to that showed by Tk2 -/-400 dCMP1dTMP .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The modification of dTMP to dTTP can take place in mitochondria ( Scheme 1 ). In the literature, it is disputed whether TS exists in mitochondria [ 16 , 17 ] or not [ 18 ]. Even RNR might also be located in mitochondria [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, both L-FAC analogs were cross-reactive with mitochondrial thymidine kinase 2 (TK2), which, like dCK, lacks enantioselectivity and consequently phosphorylates deoxypyrimidines with both D-and L-enantiomeric configurations (16). In humans, cross-reactivity with TK2 was likely responsible for the uptake of the FAC analogs into the myocardium (12), a tissue with high TK2 expression (17).…”
mentioning
confidence: 99%